Life Threatening haemoptysis in primary lung cancer-signet ring cell carcinoma. (2020) - Anwar, Shamsuddin; Acharya, Sudeep; Elsayegh, Dany; Sokoloff, Alisa; Rehan, Maryam
Abstract: Primary signet ring cell carcinoma of the lung is a rare non-small cell carcinoma of the lung with extremely aggressive features and poor prognosis. The diagnosis mainly required tissue biopsy with immunohistochemical analysis and gene mutation studies. We describe a unique case of primary signet ring cell carcinoma of the lung presenting with life threatening haemoptysis along with literature review of prognosis and management of this rare clinical entity.